PERAN GURU DALAM MEMBENTUK AKHLAK SISWA PADA ERA SOCIETY DI MI MUHAMMADIYYAH NGADIREJAN PRINGKUKU PACITAN - Yuliani, Tri (Jurnal PGSD, 2024)
The importance of forming children's character makes teachers play an important role in it. Apart from educating, teachers must also guide and be role models. The research provides a new picture of the important role of a teacher in the formation of students' morals in the 5.0 (society) era. The aim of this research is to find out how students' morals have changed in the 5.0 era, and what the role of teachers as educators is to shape students' morals and character. This research uses a qualitative method, with a descriptive approach, where data is collected using interviews and in-depth observation, so that it will provide maximum and accurate results. The results of the research are that the moral condition of MI Muhammadiyyah Ngadirejan Pacitan students is quite good in general, however there are several elements that make some students still have poor morals. The role of teachers in schools is divided into three: 1. Before the learning process: teachers as instructional designers, teachers as role models and teachers as parents. 2. In the learning process: teacher as organizer, motivator, facilitator, innovator and mentor. 3. After learning: teacher as supervisor and evaluator.